Video-Assisted Thoracoscopic Surgery for Posttraumatic Hemothorax in the Very Elderly - Schweigert, Michael; Beron, Martin; Dubecz, Attila; Stadlhuber, Rudolf; Stein, Hubert (The Thoracic and Cardiovascular Surgeon, 2012)
Objective Thoracic injury is a life-threatening condition with advanced age being an independent risk factor for both higher morbidity and mortality. Furthermore, elderly patients often have severe comorbidity and in case of chest trauma with rib fractures and hemothorax, their clinical condition is likely to deteriorate fast. Aim of this study is to investigate the feasibility and results of video-assisted thoracoscopy for the treatment of posttraumatic hemothorax in very elderly patients of 80 years or more.Methods The outcomes of 60 consecutive patients who received video-assisted thoracoscopic surgery for posttraumatic hemothorax in a German tertiary referral hospital between 2006 and 2010 were reviewed in a retrospective case study. Patients older than 80 years were identified. Results There were 39 male and 21 female patients. The median age was 63.2 years. The in-hospital-mortality was 1.7% (1/60). Fifteen of the 60 patients were 80 years or older (80–91). Main reason for hemothorax was blunt chest trauma. Altogether 23 patients had fractures of three or more ribs including six octogenarians. Elderly patients suffered from preexisting cardiopulmonary disease and were often referred to the thoracic surgeon with considerable delay. Video-assisted thoracoscopic surgery was feasible and all octogenarian patients finally recovered well without in-hospital-mortality. Conclusions Video-assisted thoracoscopic surgery for treatment of posttraumatic hemothorax shows excellent results in very elderly patients of 80 years or more. Despite severe comorbidity and often delayed surgery all patients recovered. We therefore conclude that advanced age is no contraindication for surgical management of posttraumatic hemothorax by means of video-assisted thoracoscopy.
Keywords: geriatric (includes elderly); lung; benign or congenital lesions; minimally invasive surgery (includes port access; minithoracotomy); thoracoscopy/VATS